Humble by nature : life, lambs and a dog called Badger - Humble, Kate (London : Headline Publishing, 2013)
"In 2010, television presenter Kate Humble learned that a nearby farm in the Wye Valley where she had lived for four years was set to be sold off, broken up into lots to maximize its value. Another small farm lost; another opportunity for a young, farmless farmer gone. Kate contacted the council with an alternative plan: to keep the farm a working farm. After six months of plans and endless meetings, Kate and her husband, Ludo, finally convinced the council that their plan would work, even though they hadn't the first clue of how to run a farm"--Publisher's description.
Includes index.
Keywords: Humble, Kate -- Homes and haunts -- Wales; Agriculture -- Wales; Farm life -- Wales